Side channel attack of cipher chips based on difference variability - Yang ZHANG; Kai-yan CHEN; Xiong-wei LI; Jun-guang CHEN; Yan LI (Tongxin xuebao)
Side channel attack (SCA) has the problems of high sample quantity and long analysis time. Noise of side channel leakage and its differential reduction method are researched combined with the architecture of micro control unit (MCU). Signal difference variability and hamming weight difference variability are defined, whose inverse proportion is checked. Method of key analysis based on difference variability is proposed, which uses its change property in encrypt process. Data encryption standard (DES) is cracked in experiment, which only needs 150 power tracks and 1.03 s analysis time. The attack method can be extended to crack other block ciphers which implemented in general purpose MCU.